Calculation of biogas generation by the anaerobic digestion method from biomass extracted from the Ecatepec’s central de abasto, Mexico - Martínez-Rodríguez, María Concepción (2023)
The Central de Abasto Ecatepec is the largest trade center in the municipality and houses approximately 700 businesses, it worked with a population of 84 whose main products for sale are fruits, vegetables, meats, groceries, sweets, flowers, among other things, generating around 18 tons of daily waste, 44% of which is organic. This waste is deposited in containers and then transported to garbage dumps, thus losing all kinds of energy use.   In order to take advantage of and make visible the energy capacity of these residues, as well as to promote the use and exploitation of green energies, the present investigation has been carried out, which has the objective of calculating the valuation of energy that can be obtained through the generation of methane from organic solid waste accumulated in a batch tank bioreactor through the anaerobic digestion method in the area of ​​the Central de Abasto de Ecatepec de Morelos. Under the right conditions and the use of the indicated bioreactor, the biomass generated in the study area can produce up to 517.67 kWh, a value that, although it does not cover the current energy demand in the area, would represent 22% in the use of clean energy at the Ecatepec supply center, State of Mexico.